2010
DOI: 10.1111/j.1743-6109.2010.01971.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflatable Penile Prosthesis Placement in Men with Peyronie’s Disease and Drug-resistant Erectile Dysfunction: A Single-Center Study

Abstract: Introduction Erectile dysfunction (ED) frequently accompanies Peyronie’s disease (PD) and changes the therapeutic approach. Aim To evaluate a single-center experience with inflatable penile prostheses (IPP) in men with medication refractory ED and PD. Methods Ninety men underwent placement of an IPP with straightening maneuvers as necessary to address their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 35 publications
2
87
0
1
Order By: Relevance
“…78 Although it would appear that for more severe curvature that more advanced techniques will be necessary, published experience has suggested that manual modeling may be used as first-line therapy for correction of curvature after prosthesis implantation. An alternative to this would be to perform a tunic plication such as the 16-dot suture technique contralateral to the curvature before placement of the prosthesis so as to correct curvature.…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…78 Although it would appear that for more severe curvature that more advanced techniques will be necessary, published experience has suggested that manual modeling may be used as first-line therapy for correction of curvature after prosthesis implantation. An alternative to this would be to perform a tunic plication such as the 16-dot suture technique contralateral to the curvature before placement of the prosthesis so as to correct curvature.…”
Section: Indicationsmentioning
confidence: 99%
“…Recently Levine et al 78 reported on 90 consecutive men undergoing placement of an inflatable penile prosthesis, with 4% having satisfactory straightening with prosthesis placement alone, 79% having satisfactory curvature correction with prosthesis and modeling, 4% required tunical incision and 12% had incision and pericardial grafting for correction of curvature. It did not appear that the additional maneuvers increased the rate of mechanical failure or infection.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 It has become the predominant method utilized in the United States for penile straightening during IPP placement. 56,64,65 If curvature > 30º persists, subsequent plaque-releasing incisions, transcorporeal techniques (transcorporeal incision, scratch procedure) or grafting are also usually needed. Grafting is recommended for tunical defects greater than 2 cm preventing prostheses herniation.…”
Section: Penile Prosthesismentioning
confidence: 99%
“…[1] Corporeal fibrosis may develop following the explantation of infected penile prosthesis, refractory low-flow priapism, severe penile trauma, penile irradiation, Peyronie's disease, and chronic intracavernosal injection of vasoactive drugs. [1][2][3][4][5][6] In such cases, reinforcement of blind dilatation against a resistance may lead to perforation through the glans or urethra. Because of the problems mentioned above, most surgeons tend to implant smaller cylinders to minimize the complications that probably results in penile shortening of up to 4-6 cm.…”
Section: Introductionmentioning
confidence: 99%